Supremasi Hukum dan Demokrasi - Bambang Sugiono; Ahmad Husni MD (Fakultas Hukum Universitas Islam Indonesia, 2000)
The government administration laid upon the principle of people's sovereignty is absolutely in need of the enforcement of law supremacy as well as the clear democracy mechanism. The enforcement of law supremacy itself depends on the visibility and the accuracy of the regulation of law and legislation for government, representative, and judicial institutions, and the assurance of law protection for individuals (citizens) against the behavior of authorityandsocialaction which contradict with the norms of law as well. In undertaking the enforcement of law supremacy dan democracy, the cultural aspect must be put in line with the quality of substance one. This effort is greatly needed in arranging conflicts so that the maturation of democracy through law enforcement can be consistent and fair.